2.3 µm laser potential of TeO2 based glasses. (23rd August 2017) - Denker, B I; Dorofeev, V V; Galagan, B I; Motorin, S E; Sverchkov, S E
Abstract: Tm 3+ doped TeO2 -based well-dehydrated glasses were synthesized and investigated. The analysis of their spectral and relaxation properties have showed that these glasses can be a suitable host for bulk and fiber lasers emitting at 2.3 µ m wavelength ( 3 H4 – 3 H5 Tm 3+ transition). Laser action in the bulk glass sample was demonstrated.